The Effect of Demand-Side Issues in Accessing External Funds on Performance of SMEs in Thailand - Naruanard Naruanard; Bernice Kotey (Jurnal Ilmiah Ekonomi Bisnis, 2011)
Several factors have been identified in the literature as affecting SME performance, in particular ability to access finance. Access to finance is in turn influenced by variables in both the enterprise’s internal and external environment. It is held that SMEs are unable to access external finance because they are not investment ready. They lack the necessary information and knowledge of their businesses to approach finance providers or to be successful in accessing funds if they do. Face-to-face interviews using structured questionnaire were conducted to collect primary data from 407 SMEs operating in the trading sector in 3 provinces-Bangkok, Chiang Mai and Khon Kan. Results of the structural equation modelling (SEM) reveal that quality of financial information has significant positive effect on performance and on owner-managers’ perception of their ability to access external capital. A significant positive effect of ability to access capital on performance was also found.